PENYULUHAN KESEHATAN REPRODUKSI REMAJA DALAM RANGKA PENCEGAHAN STUNTING DI DESA KESEK KECAMATAN LABANG - Santoso, Eko Budi; Gunawan, Bambang; Hidayati, Nurul; Werdini, Yoessy Etna; Hariyanto, Ahmad; PS, Alaika Bagus Kurnia; Khodijah, Unziya (LP2M STP Mataram, 2024)
Adolescence are part of an age group from 10 years to before the age of 18 years. Efforts to maintain adolescent health aim to prepare adolescents to become healthy, intelligent, high-quality and productive adults and to participate in maintaining, nurturing and improving their health. Adolescent health is very important to pay attention to because during adolescence, teenagers experience significant changes physically, psychologically and socially. Adolescent health efforts include positive coaching, accident prevention, violence prevention, reproductive health, prevention and control of infectious diseases and prevention of non-communicable diseases, nutrition and physical activity, mental health, and adolescent health in crisis situations. This community service takes the topic of reproductive health to increase participants' knowledge about reproductive health. This community service method uses an educational approach through counseling with a total of 38 teenagers who are members of the community from Kesek Village, Labang District. Counseling is carried out by involving lecturers whose expertise is adapted to the problem. The results of the counseling showed a significant increase in participants' knowledge as demonstrated by the post-test results. Participants in the good category increased in number from 3 people (13,2%) at the pre-test to 26 people (68,4%) at the post-test. The results of the outreach found that many teenagers still do not care about reproductive health problems associated with stunting cases. The impact of the service is that there is an increase in teenagers' knowledge regarding efforts to prevent stunting disease related to reproductive health. For this reason, teenagers need to make preventative efforts by maintaining their diet and carrying out early examinations at the nearest health service